2021
DOI: 10.1155/2021/9929093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets and Mechanisms of Scutellariae radix-Coptidis rhizoma Drug Pair for the Treatment of Ulcerative Colitis Based on Network Pharmacology and Molecular Docking

Abstract: This study aims to analyze the targets of the effective active ingredients of Scutellariae radix-Coptidis rhizoma drug pair (SCDP) in ulcerative colitis (UC) by network pharmacology and molecular docking and to explore the associated therapeutic mechanism. The effective active ingredients and targets of SCDP were determined from the TCMSP database, and the drug ingredient-target network was constructed using the Cytoscape software. The disease targets related to UC were searched in GeneCards, DisGeNET, OMIM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Network pharmacology is an excellent tool to construct a drug-target network and reveal the underlying mechanisms of TCM. Spleen deficiency was regarded as the original cause of UC based on TCM theory [ 27 ]. Additionally, spleen deficiency and liver stagnation are the root causes of IBS [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is an excellent tool to construct a drug-target network and reveal the underlying mechanisms of TCM. Spleen deficiency was regarded as the original cause of UC based on TCM theory [ 27 ]. Additionally, spleen deficiency and liver stagnation are the root causes of IBS [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a proinflammatory factor, IL-23 is involved in the formation and expansion of IL-17. When the IL-23/IL-17 inflammatory axis is formed, the inflammatory response continues to expand [ 29 ]. In addition, Peter et al found that the IL-33/ST2 axis can aggravate Dss-induced colitis and IL-33 can specifically induce the activation of key pathogenic cytokines including IL-17 and IL-13 and maintain and amplify the inflammatory response of the IL-17 signaling pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the adverse effects of first-line treatment, it is urgent to find safe and effective alternative medicines. Numerous studies have demonstrated that CR can ameliorate UC and its complications ( Niu et al, 2021 ; Xie et al, 2022 ; Yang Y et al, 2022 ). However, the therapeutic mechanism of CR exerted on UC has not been scientifically and systematically elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…As a natural medicine, Coptidis Rhizoma (CR) has been used to alleviate the notable symptoms of UC for thousands of years in China, such as bloody diarrhea, tenesmus and abdominal pain ( Wang et al, 2020 ; Lu et al, 2021 ; Niu et al, 2021 ). Previous studies have demonstrated that CR has the pharmacological effects of anti-inflammatory, anti-bacterial, anti-oxidant, anti-tumor and other pharmacological effects ( Nagajyothi et al, 2014 ; Kwon et al, 2021 ; Kang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%